Description of two new species of Lycinus (Araneae: Nemesiidae) - Sylvia M. Lucas; Rafael P. Indicatti (Zoologia (Curitiba), 2010)
Two new species of Lycinus Thorell, 1894 are described in this paper, L. portoseguro sp. nov. and L. choros sp. nov. Lycinus portoseguro sp. nov. is based on male and female from Porto Seguro, state of Bahia, Northeastern Brazil. This is the first record of a species of Lycinus from Brazil. Males of L. portoseguro sp. nov. differ from the remaining species of the genus by the presence of a retrolateral megaspine on tibia I and by the short embolus. Females can be distinguished by the scopulae divided on tarsi II. Lycinus choros sp. nov. is based on one male from La Serena, IV Region (Coquimbo), Chile. It is the eighth species described from this country. L. choros sp. nov. resembles L. epipiptus (Zapfe, 1963) by the longer embolus and differs from it by the short palpal tibia and by the scopulae undivided on male tarsi I-II.